EVALUATION OF CHARCOAL MARKETING IN IBARAPA CENTRAL LOCAL GOVERNMENT AREA OF OYO STATE - T.A, Adeagbo; S.A, Amao; Z.O, Oluwafemi; Z.O, Oluwafemi; O.M., Olayiwola (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The cry for alternative energy sources due to the effects of global warming has put charcoal in the forefront of the global market and the rate at which the prices of petrol, gasoline and gas are changing at geometric progression has made majority of low income earners to shift from all these expensive sources of energy to charcoal and this has made charcoal marketing to gain upper hand in the economy. The data for this research work was of primary source through the use of structure questionnaires and simple random sampling technique was used to select 100 charcoal marketers in Ibarapa Central Local Government Area of Oyo State. The data collected were subjected to descriptive statistics, double log functional form of ordinary least square, gross margin and gini coefficient techniques. The result revealed that age, sex, educational level, household size and years of experience have great influence on the profitability of charcoal marketing. The adjusted R square reveals that the independent variables have explained 90.70% variation of the total revenue while the remaining 9.30% might be due to error term. Also, the acquisition and transportation costs gulped 60.44% and 34.79% of the total variable cost. Average total variable cost and average total revenue are ₦59,111 and ₦72,882.50 respectively. This indicates that an average marketer earned ₦13,770 as gross margin/truck suggesting that charcoal marketing is profitable in the study area. GiniCoefficient of 0.3854 indicates high level of concentration and consequently high inefficiency in the market structure.